Multiparty Politics Dynamics in Uganda - Kakuba, Sultan Juma (African Journal of Political Science and International Relations, 2010)
In liberal democracy, it is obvious political parties play a critical role in deepening democratic process. Besides, providing veritable avenue for popular participation, they are celebrated mechanism for political mobilization, guiding policy formulation, implementation and much more significant guards against dictatorship. In Uganda, there is evidence that political parties have not been adequately institutionalized. This can be seen in a manner in which they have process in the country. The efforts of political parties to woo supporters in the hope of making a mark at various levels of government, overheats the polity. This been attempting to foster democratic governance in the past and how their current revival to practice multiparty politics fails to strengthen democratic paper advances the position of political parties in furthering democracy in Uganda. It suggests that the current activities of political parties are ill equipped in broadening democratic dividends.
Keywords: Political parties, democracy and governance